Factors determining customers revisit intention to dine at upscale Malay ethnic restaurants in Kuala Lumpur / Abdullah Muhamed Yusoff - Muhamed Yusoff, Abdullah (2013)
Research on food and eating out behavior as an expression of taste and attitude is a recent phenomenon. In order to compete, foodservice operators must understand what the important elements for survival are. In any affluent society, necessity and luxury in consumption behavior is constantly been redefined. Society with high income will definitely expect more to satisfy them. The purpose of this study is to examine the impact of three elements of foodservice quality dimensions such as physical environment, staff behavior and food quality on customer satisfaction as mediating variable and customer revisit intention as dependent variable. A self administered subset of questionnaire are distributed and analyzed with SPSS version 20.0 software. Data were collected from the diners at upscale Malay ethnic restaurants which is located at Kuala Lumpur, Malaysia. The results of the independent variables such physical environment, staff behavior and food quality are significant when determinant the customer satisfaction and revisit intention. Thus, the study finding greatly help the researchers and practitioner understand the complex relationship among the foodservice quality (physical environment, staff behavior and food quality) especially to the Malay upscale restaurants industry in Malaysia. The implication of the study is discusses to develop uniqueness marketing strategies to enhance the local operator being competitiveness among other restaurant operators.